Just Negotiation - Rebecca Hollander-Blumoff (Washington University Law Review, 2010)
This Article argues that the procedural justice—that is, fairness of process—plays a critical and largely unexamined role in legal negotiation, encouraging the acceptance of and adherence to negotiated agreements. An economic focus has dominated prior work on legal negotiation and has largely touted the importance of negotiated outcome rather than process. This Article marshals theoretical support for the role that procedural justice may play in bilateral legal negotiation and supports the theoretical case with empirical data from social psychology. A robust empirical literature has established that procedural justice has a significant effect on individuals’ perceptions of their outcomes in third party decision-making systems, encouraging acceptance of and adherence to outcomes and fostering a perception that decision-making systems are legitimate. Recently, such empirical work has begun to consider the effects of procedural justice in a setting without a third-party decision maker. These newest empirical findings support an increased role for fairness of process in negotiation. The Article concludes by exploring the complexities of taking procedural justice effects in negotiation seriously in light of the fact that legal negotiation is conducted by agent (the attorney), rather than principal (the client).
Keywords: Negotiation; Procedural justice; Fairness; Attorney & amp; client